2017
DOI: 10.11648/j.ab.20170505.13
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant and Antimicrobial Activities of Exopolysaccharides from Yoghurt Starter

Abstract: Abstract:The in vitro antimicrobial and antioxidant activities of the exopolysaccharide (EPS) extracted from yoghurt starter were investigated. Antimicrobial activity tests were carried out using disc diffusion methods with Escherichia coli, Staphylococcus aureus and Streptococcus D, Proteus spp and the yeast of Candida albicans. The antioxidant properties were evaluated using the test of DPPH free radical trapping. The results show that the EPS has weak antimicrobial activity against the tested strains with i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 19 publications
(24 reference statements)
4
5
0
Order By: Relevance
“…This result is in agreement with Zhang et al [26] in which it was reported that EPS produced by Lactobacillus plantarum showed a DPPH scavenging activity of 52.23% at 1000 µg/mL. Similarly, Ghalem [27] documented a DPPH radical scavenging of 24.25% from EPS produced by yoghurt starter culture. In contrast, Xu et al [28] reported that the DPPH radical scavenging activity of the EPS isolated from Bifidobacterium animalis could increase with the increasing EPS concentration and reach to a similar activity with ascorbic acid.…”
Section: Dpph Free Radical Scavenging Activity Of the Epssupporting
confidence: 92%
“…This result is in agreement with Zhang et al [26] in which it was reported that EPS produced by Lactobacillus plantarum showed a DPPH scavenging activity of 52.23% at 1000 µg/mL. Similarly, Ghalem [27] documented a DPPH radical scavenging of 24.25% from EPS produced by yoghurt starter culture. In contrast, Xu et al [28] reported that the DPPH radical scavenging activity of the EPS isolated from Bifidobacterium animalis could increase with the increasing EPS concentration and reach to a similar activity with ascorbic acid.…”
Section: Dpph Free Radical Scavenging Activity Of the Epssupporting
confidence: 92%
“…Findings from this study also support observation by Nyanzi, Shuping, Jooste, and Eloff (2015) contributed by exopolysaccharides (EPS) (Ghalem, 2017;Zhang et al, 2012).…”
Section: Discussionsupporting
confidence: 87%
“…The antioxidative activity of Lactobacillus spp. is mostly contributed by exopolysaccharides (EPS) (Ghalem, ; Zhang et al., ).…”
Section: Resultsmentioning
confidence: 99%
“…In this work, microorganisms isolated from seawater of Mauritius were screened for their ability to produce polysaccharides which exhibit antibacterial properties. Several authors have reported on the potential of exopolysaccharides as antimicrobial agents (Wilson et al 2011;Karlapudi et al 2016;Wu et al 2016) and this property was demonstrated for EPS obtained from different types of microorganisms (Ghalem 2017;Jeong et al 2017). Similarly, in this study, eight selected marine isolates were shown to produce EPS which could successfully inhibit the growth of human pathogenic bacteria.…”
Section: Discussionsupporting
confidence: 61%
“…More recently, biological activities of exopolysaccharides have been reported, with a number of recent studies documenting their immunostimulatory, antiviral, anti-oxidative, anti-tumour and antibacterial properties (Balzaretti et al 2017;Zhou et al 2017;Reichert et al 2017;El-Deeb et al 2018;Wen et al 2018). The latter represents an interesting prospect in view of the increasing resistance of pathogenic microorganisms to existing antibiotics (Ghalem 2017). Indeed, drug-resistant microorganisms have become an increasing concern and the potential of microbial exopolysaccharides in fighting microbial resistance lies both in their intrinsic biological activities and their ability to be used in drug delivery systems (El-Naggar et al 2016;Sezer et al 2017).…”
Section: Introductionmentioning
confidence: 99%